(Re)Mapping the centres Membership and State - Trevor Harris (dir.) (Presses universitaires François-Rabelais, 2000)
How is it possible to belong to a territory when its boundaries are no longer exclusively physical? How can we define the centre, or allegiance to that centre, at the beginning of the third millennium, if that centre cannot hold? 2In an age when appeals are made both to sovereignty and ""the global village"", when terms such as ""subsidiarity"" and ""the international community"" have become common currency, the notion of membership is irrevocably plural. 3This obviously invites reflection upon t...